2016
DOI: 10.1007/s00535-016-1170-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture with intestinal epithelial organoids allows efficient expansion and motility analysis of intraepithelial lymphocytes

Abstract: BackgroundIntraepithelial lymphocytes (IELs) in the intestine play important roles in the regulation of local immune responses. Although their functions have been studied in a variety of animal experiments, in vitro studies on spatiotemporal behaviors of IELs and their interaction with intestinal epithelial cells (IECs) have been hampered due to the lack of a suitable culture system. In this study, we aimed at developing a novel co-culture system of IELs with IECs to investigate dynamic interaction between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
139
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 29 publications
2
139
0
1
Order By: Relevance
“…IELs do not recirculate and that intestinal epithelial space provides the & Atsushi Mizoguchi mizoguchi_atsushi@med.kurume-u.ac.jp final destination of T cells [3,4]. In addition, the authors demonstrate another novel finding that, during the movement, IELs can continuously change their cellular shapes [8]. As compared to the in vivo system, the organoid-based in vitro co-culture system therefore may provide a more useful tool to closely examine the interaction of epithelial cells and IELs at a cellular level.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…IELs do not recirculate and that intestinal epithelial space provides the & Atsushi Mizoguchi mizoguchi_atsushi@med.kurume-u.ac.jp final destination of T cells [3,4]. In addition, the authors demonstrate another novel finding that, during the movement, IELs can continuously change their cellular shapes [8]. As compared to the in vivo system, the organoid-based in vitro co-culture system therefore may provide a more useful tool to closely examine the interaction of epithelial cells and IELs at a cellular level.…”
mentioning
confidence: 85%
“…IELs are found to migrate into, and then come out from, the organoids [8]. This finding is certainly of interest because it challenges current concepts that TCRcd ?…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Co-culture of organoids with intraepithelial lymphocytes (IELs) (Nozaki et al, 2016;Zumwalde et al, 2016) has opened up the possibility of exploiting organoids to expand immune cells in vitro, which could be used for immunotherapy purposes, for instance by predicting cytotoxicity when cultured together with patient-derived tumor organoids. IELs play important roles in local immune responses in the tissue in which they reside and could potentially be triggered to specifically attack tumor cells.…”
Section: Immunotherapymentioning
confidence: 99%
“…IELs play important roles in local immune responses in the tissue in which they reside and could potentially be triggered to specifically attack tumor cells. Nozaki et al established a novel strategy to maintain and expand IELs in a co-culture system with murine small intestinal organoids (Nozaki et al, 2016). Importantly, the authors showed that IEL migration dynamics are comparable to those of IELs residing in an in vivo setting, suggesting that IELs do not lose functional activity in vitro.…”
Section: Immunotherapymentioning
confidence: 99%